A Resolution of the Variability Discrepancy Between Peak Ground Acceleration and Spectral Stress Drop - Shota Shimmoto (The Seismic Record)
It has been recognized that the between-event variability of peak ground acceleration (PGA) is significantly smaller than the variability of the stress drop calculated from corner frequency (the spectral stress drop). Resolving this discrepancy is indispensable for improving seismic hazard assessment because the spectral stress drop is considered a fundamental parameter for predicting high-frequency ground motions. This study addresses this paradox for Mw 3.6–7.1 crustal earthquakes in Japan. Two factors are essential for resolving the problem: (1) calculating the spectral stress drop using a high-frequency-fitted corner frequency (called the stress parameter Δσfch) and (2) considering the magnitude dependence of Δσfch. To estimate Δσfch, the source spectra for crustal earthquakes in Japan are obtained using the two-stage spectral ratio method, which enables the estimation of double-corner-frequency spectra. This two-stage approach is more effective for accurately estimating Δσfch than the standard spectral ratio approach that assumes the single-corner frequency model. This study shows that Δσfch increases with increasing magnitude up to Mw∼5.5 and then becomes constant. The variability of Δσfch calculated by considering this magnitude dependence of Δσfch aligns with the between-event variability of PGA. Incorporating a double-corner-frequency model is crucial for predicting ground-motion variability and enhancing seismic hazard assessments.